The Influence of Intellectual Ability, Discipline and Work Motivation on Teacher Performance in Senior High School (SMAN) 1 Karang Baru Aceh, Tamiang Regency - Tengku Muhammad Sahudra (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The formulation of the problem in this study is how the influence of intellectual ability on teacher performance in Senior High School 1 of Karang Baru, Aceh Tamiang Regency. How is the influence of discipline on teacher performance in Senior High School 1 of Karang Baru, Aceh Tamiang Regency. What is the influence of work motivation on teacher performance in Senior High School 1 of Karang Baru, Aceh Tamiang Regency. How is the influence of intellectual ability, discipline and work motivation on teacher performance in Senior High School 1 of Karang Baru, Aceh Tamiang Regency. The purpose of this study was to determine the effect of intellectual ability on teacher performance. To determine the effect of discipline on teacher performance. To determine the effect of work motivation on teacher performance. To determine the effect of intellectual ability, discipline and work motivation on teacher performance. The sample in this study amounted to 50 teachers. The data analysis technique used is multiple linear regression analysis. The results of this study are intellectual ability, discipline and work motivation simultaneously have a positive and significant effect on teacher performance Senior High School 1 of Karang Baru, Aceh Tamiang Regency because the value of F count> Ftable is (53,510> 2,960). Partial intellectual ability has a positive and significant effect on teacher performance in Senior High School 1 of Karang Baru, Aceh Tamiang Regency because of the tcount> t table (2,918> 1,680). Partial discipline has a positive and significant effect on teacher performance Senior High School 1 of Karang Baru, Aceh Tamiang Regency because of tcount> ttable (8,991> 1,680). Partial work motivation has a positive and significant effect on teacher performance Senior High School 1 of Karang Baru, Aceh Tamiang Regency because of the tcount> ttable (2,918> 1,680). Intellectual ability, discipline and work motivation simultaneously influence the performance of teachers in Senior High School 1 of Karang Baru, Aceh Tamiang Regency at 76.30% and the remaining 32.70% influenced by other factors not examined.